Enhancing the Quality of Education through Information Technologies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The current stage of educational development emphasizes the wide integration of computer technologies into the learning process. They provide opportunities for advancing teaching to a new level, opening up possibilities that were previously inaccessible for both teachers and students. Information technologies are utilized in various fields of education, aiding not only in specialized topics but also in enhancing the overall understanding of subjects being taught.